Understanding HIV‐related Stigma Among Indonesian Nurses. (January 2015) - Waluyo, Agung; Culbert, Gabriel J.; Levy, Judith; Norr, Kathleen F.
Abstract : N/A: Evidence indicates widespread stigmatization of persons living with HIV (PLWH) in Indonesia. Such attitudes among health care workers could impede the country's policies for effective diagnosis and medical treatment of PLWH. Nonetheless, research to guide interventions to reduce stigma in health care settings is lacking. Also, the contributions of workplace, religion, and HIV knowledge to nurses' HIV‐related stigma are poorly understood. Our cross‐sectional study aimed to describe factors associated with nurses' stigmatizing attitudes toward PLWH. Four hundred nurses recruited from four hospitals in Jakarta, Indonesia, were surveyed using the Nurse AIDS Attitude Scale to measure stigma. Stigmatizing attitudes were significantly predicted by education, HIV training, perceived workplace stigma, religiosity, Islamic religious identification, and affiliation with the Islamic hospital. HIV knowledge was not a significant predictor of stigmatizing attitudes. Organization changes fostering workplace diversity are likely to substantially reduce stigmatizing attitudes in nurses.